Struggles for citizenship in Africa - Manby, Bronwen (London Zed Books, 2009)
Hundreds of thousands of people living in Africa find themselves non-persons in the only state they have ever known. Because they are not recognised as citizens, they cannot get their children registered at birth or entered in school or university; they cannot access state health services; they cannot obtain travel documents, or employment without a work permit; and if they leave the country they may not be able to return. Most of all, they cannot vote, stand for office, or work for state institutions. Ultimately such policies can lead to economic and political disaster, or even war. The conflicts in both Cote d'Ivoire and the Democratic Republic of Congo have had at their hearts the very right of one part of the national population to share with others on equal terms the rights and duties of citizenship. This book brings together new material from across Africa of the most egregious examples of citizenship discrimination, and makes the case for urgent reform of the law.
Includes bibliographical references and index.
Keywords: Citizenship -Africa.